Promoting Social Dialogue in European Organizations: Human Resources Management and Constructive Conflict Management - Euwema, Martin; Munduate, Lourdes; Elgoibar, Patricia; Pender, Erica; Belén García, Ana (Industrial Relations & Conflict Management, 2015)
Industrial, Organisational and Economic Psychology; Social Policy; Political Science, general